Attractiveness of citrus pulp and orange albedo extracts to Atta sexdens rubropilosa (Hymenoptera: Formicidae) - Verza, Sandra S. [UNESP]; Forti, Luiz Carlos [UNESP]; Matos, Carlos A. O. [UNESP]; Garcia, Marise G. [UNESP]; Nagamoto, Nilson S. [UNESP] (My University, 2006)
The present study aimed to compare the attractiveness of industrial citrus pulp with the handmade orange albedo to the workers of Atta sexdens rubropilosa. For this, filter paper fragments were impregnated with organic extracts obtained through chemical extraction and sequential fractioning with hexane and dichloromethane and offered to different field nests. It was verified that the industrial citrus pulp extract is as good as the handmade orange albedo extract. This preference is discussed keeping in mind the chemical, behavioral and nutritional factors.
Keywords: Albedo; Atta sexdens rubropilosa; Attractiveness; Citrus pulp; Leaf-cutting ants; Atta; Citrus; Formicidae; Hymenoptera